The Influences of Adherence to Tamoxifen and CYP2D6 Pharmacogenetics on Plasma Concentrations of the Active Metabolite (Z)‐Endoxifen in Breast Cancer. Issue 2 (9th November 2019) - Nardin, Jeanine Marie; Schroth, Werner; Almeida, Thais Abreu; Mürdter, Thomas; Picolotto, Solane; Vendramini, Evelyn Castillo Lima; Hoppe, Reiner; Kogin, Jenifer Primon; Miqueleto, Diandra; de Moraes, Silvia Dark Robaskievicz; Schwab, Matthias; Pecoits‐Filho, Roberto Flavio; et al.
Abstract : Tamoxifen efficacy in breast cancer is suspected to depend on adherence and intact drug metabolism. We evaluated the role of adherence behavior and pharmacogenetics on the formation rate of (Z)‐endoxifen. In 192 Brazilian patients, we assessed plasma levels of tamoxifen and its metabolites at 3, 6, and 12 months of treatment (liquid‐chromatography tandem mass spectrometry), adherence behavior (Morisky, Green, and Levine medication adherence scale), and cytochrome P450 2D6 (CYP2D6) and other pharmacogene polymorphisms (matrix‐assisted laser‐desorption‐ionization time of flight) mass spectrometry, real‐time polymerase chain reaction). Adherence explained 47% of the variability of tamoxifen plasma concentrations ( P < 0.001). Although CYP2D6 alone explained 26.4%, the combination with adherence explained 40% of (Z)‐endoxifen variability at 12 months ( P < 0.001). The influence of low adherence to not achieving relevant (Z)‐endoxifen levels was highest in patients with noncompromised CYP2D6 function (relative risk 3.65; 95% confidence interval 1.48–8.99). As a proof‐of‐concept, we demonstrated that (Z)‐endoxifen levels are influenced both by patient adherence to tamoxifen and CYP2D6, which is particularly relevant for patients with full CYP2D6 function.